Evaluating social equity and conservation attitudes in community based conservation: a case study of the controlled hunting area program in the Bale Mountains of Ethiopia - Astella, Bethlehem Abebe, author; Jones, Kelly, advisor; Evangelista, Paul, advisor; Solomon, Jennifer, committee member; Galvin, Kathleen, committee member (Colorado State University. Libraries, 2021)
This dissertation research examines perceptions of social equity and conservation attitudes in community-based conservation (CBC) programs in the Bale Mountains, Ethiopia. While there has been an increasing shift towards inclusive and participatory approaches in conservation over the past 40 years, the social and environmental outcomes of CBC programs remain limited. One reason for this is the failure to recognize the diversity of local actors involved in CBC programs, the different costs and benefits they face, and how embedded power relations shape participation and empowerment in CBC programs. Devising effective and fair CBC programs requires putting social equity concerns at the core of conservation, which should in turn improve both social and conservation outcomes. This dissertation makes conceptual, methodological, and empirical contributions to the fields of social equity and CBC by implementing a mixed methods assessment of perceptions of social equity and conservation attitudes, as indicators of long-term conservation outcomes, and the factors that influence these perceptions and attitudes. Specifically, Chapter 1 provides an overview of the dissertation starting with a background of the underlying premises and implementation challenges of CBC programs globally and in Ethiopia. The chapter introduces social equity and conservation attitudes as central themes of the dissertation, gives a backdrop of the community-based controlled hunting area program in the Bale Mountains, and highlights the key research questions. In Chapter 2, this dissertation draws from a multi-dimensional social equity framework to generate a nuanced understanding of different groups' perceptions of equity in the distribution of benefits and costs, the processes of engagement and participation, and the recognition of needs and priorities in a CBC program. I conducted 15 focus group discussions in different communities and apply grounded theory to elicit locals' nuanced perceptions of social equity. The chapter underscores the need to evaluate local actors' diverse and contextualized relationships with other actors and the natural world and give recognition to how perceptions of equity interplay with broader social and environmental processes, in designing and implementing CBC programs. For Chapter 3, I conducted household surveys in four communities. This chapter builds on the previous qualitative analysis by assessing the effects of socio-economic and institutional factors in shaping perceptions of equity across different communities and CBC program models. I integrate the Sustainable Livelihoods Framework (SLF) to assess how access to various capital assets influences equity perceptions. The results signify the need to address the heterogeneity among local actors affected by conservation programs in equity design and assessment. These findings further highlight the need to strengthen weak institutional ties with external organizations, facilitate intra-community organization, and design programs that emphasize transparency to facilitate more equitable conservation outcomes. Finally, in Chapter 4, I use household survey responses to assess how conservation attitudes vary across different communities based on different social, economic, and/ or institutional characteristics. I also examine the role of social equity in mediating how social capital affects conservation attitudes. To foster positive conservation attitudes, results suggest CBC programs need to build on and strengthen internal communal institutions and external links with conservation organizations. The findings also emphasize the need for adopting equity conscious designs that recognize the needs and priorities of marginalized groups. Overall, this dissertation contributes to the science and practice of CBC in Ethiopia and beyond. Empirically, the dissertation advances the contribution of mixed methods in assessing the complex construct of social equity. The focus group discussions with different community members and the use of grounded theory helped elicit local people's nuanced and contextualized perceptions of social equity. Informed by these qualitative findings, I developed locally relevant indicators to quantitatively measure equity perceptions across communities and program models. This contributes to the literature on social equity by adopting and refining existing frameworks in ways that are pertinent to specific contextual realities. From a policy perspective, the findings suggest that CBC programs in Ethiopia need to critically address differences in access to resources and decision-making power and to reframe notions of benefits to encapsulate multiple dimensions of equity. Additionally, the findings from this dissertation suggest that CBC programs more broadly will benefit from building internal social capital and strengthening links with external conservation organizations and resource management agencies, as social capital is key in crafting more equitable CBC programs and influencing positive conservation outcomes.
Keywords: conservation attitudes; social equity; controlled hunting; community based conservation